2016
DOI: 10.1074/jbc.m116.719682
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Action of PGC-1-related Coactivator (PRC) and c-MYC in the Stress Response to Mitochondrial Dysfunction

Abstract: PGC-1-related coactivator (PRC) has a dual function in growth-regulated mitochondrial biogenesis and as a sensor of metabolic stress. PRC induction by mitochondrial inhibitors, intracellular ROS, or topoisomerase I inhibition orchestrates an inflammatory program associated with the adaptation to cellular stress. Activation of this program is accompanied by the coordinate expression of c-MYC, which is linked kinetically to that of PRC in response to multiple stress inducers. Here, we show that the c-MYC inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…PRC, which is expressed ubiquitously, also enhances the gene transcription of NRF1. PRC mainly regulates gene expression in proliferating cells and in growth‐regulated mitochondrial biogenesis . PRC depletion results in the aggregation of atypical mitochondria and severe respiratory chain dysfunction …”
Section: Mitochondrial Biogenesis and Its Regulatorsmentioning
confidence: 99%
“…PRC, which is expressed ubiquitously, also enhances the gene transcription of NRF1. PRC mainly regulates gene expression in proliferating cells and in growth‐regulated mitochondrial biogenesis . PRC depletion results in the aggregation of atypical mitochondria and severe respiratory chain dysfunction …”
Section: Mitochondrial Biogenesis and Its Regulatorsmentioning
confidence: 99%
“…PRC1 is a relevant regulator of mitochondrial function in cells where PGC-1α is absent and mediates the activation of respiratory genes through transcription factors (101). However, the physiological role of PRC1 is still debated (102). Similar to PGC-1α, PRC1 also binds to nuclear transcription factors implicated in the expression of mitochondrial function, including NRF-1, cAMP response element-binding protein 1 (CREB) and estrogen-related receptor alpha (ERRalpha) (103).…”
Section: No Synthesis and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Thus depending on the cell type, we can have different isoforms acting in similar pathways. More recently, it was found that PRC1 and c-MYC can act in concert to reprogram gene expression in response to mitochondrial stress, providing an additional link between PRC1 and cancer (102)(Fig.3). …”
Section: No Synthesis and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Peroxisome proliferators activated receptor gamma co-activator 1 alpha (PGC-1α), known to be the regulatory master in orchestrating mitochondrial biogenesis, has been shown to be mediated by GSK-3β in mitochondria [4]. Phosphor-inactivation of GSK-3β induces the expression of PGC-1-related coactivator (PRC), which is involved in both mitochondrial biogenesis and sensitivity of metabolic stress [5]. Recently, GSK-3β signaling has been demonstrated to be implicated in regulation of mitochondrial permeability transition pore (mPTP) opening, controlling cell fates [6].…”
Section: Introductionmentioning
confidence: 99%